(untitled) (Revista Educação, Artes e Inclusão, 2023)
Printmaking, like traditional visual expressions, has expanded its technical and conceptual repertoire as a result of experiments and investigations carried out in the last fifty years (MORO, 2017). Throughout this text, it intends to show that Ecological Printmaking (EP), a product of this expansion, has influenced the emergence of new procedures introduced in Basic Education I, contributing to the development of a sensitive perception and an ethical conscience and conduct of students, in their relationship with the environment. Seeks to identify in these process of choosing disposable materials, the creative management in the making of matrices, highlighting how the concept of sustainability is applied in school artistic practices. (AGUILAR MORENO, 2017) and its progress as a training tool for citizenship. Finally, based on these contributions, highlights the effective relation of EP with the skills required by the new curricular standards known as the Common Core State Standards (BNCC in the Portuguese acronym), including experimenting with different forms of artistic expression, making sustainable use of conventional and unconventional materials, instruments, resources and techniques. (BNCC, 2017).